Ocena możliwości wykorzystania technologii mobilnego skanowania laserowego do identyfikacji drzew i ich wymiarów na przykładzie wybranych drzewostanów bukowych - Zajączkowski, Grzegorz; Falkowska, Aleksandra (Leśne Prace Badawcze, 2025)
This article evaluates the usefulness of mobile laser scanning technology (MLS) for determining selected tree and stand parameters. Usefulness was determined based on measurements taken with the Zeb-Horizon mobile scanner in four beech stands located in different parts of the country. For each stand, an XYZ point cloud was acquired and reference measurements of tree diameter at breast height (DBH) were taken. The data analysis involved processing the acquired MLS data and comparing it with the reference data. Preliminary tree location plans were prepared for the individual plots, and their accuracy was verified during subsequent fieldwork. The proportion of correctly identified trees ranged from 95.2% to 100%, with underestimation mainly affecting trees with small DBH (7–10 cm). The average differences between the mean DBH measured with the MLS technology and with a caliper were small and ranged from -4.0% to 0.3% (1 mm to 16 mm) for individual stands. Overestimation of DBH mainly affected thinner trees (up to 10 cm DBH), while underestimation affected thicker trees. Despite the high value of the coefficient of determination R2 (correlation of 0.9435 to 0.9945 for MLS data compared to reference data), only for one plot were the differences between these data in the Wilcoxon test non-significant. Differences in average DBH cross-sectional area calculated from the two methods ranged from 0.19% to -8.37% for individual stands and -2.86% on average for all trees. The greatest differences were found in a stand located on a mountain slope, where a large section had dense undergrowth. Such stand structure made it difficult to remotely detect the position of breast height on the point cloud. The results confirmed that the MLS technology can be applied in forest inventory. This method, due to the accuracy of the acquired data as well as the speed of its acquisition, can be an important alternative to traditional methods of measuring trees and stands.